Anisotropy of effective thermal conductivity analysis of heat transfer coefficient distribution around spherical particles in a packed bed - Asakuma, Yusuke; Asada, Masahiro; Kanazawa, Yushin; Yamamoto, Tsuyoshi (Computer Assisted Methods in Engineering and Science, 2015)
Effective thermal conductivity with radiation is analyzed by a homogenization method. The method used can precisely represent the conditions around particles in a packed bed. In this study, the effects of variation in parameters such as heat transfer coefficient distribution around spherical particles in a packed bed, Reynolds number, temperature and particle size on the conductivity were estimated in order to elucidate the heat transfer mechanism of complex packed structures. The results show that it is unnecessary in heat transfer analysis to consider the anisotropic behavior of the flow direction for larger particles, high Reynolds numbers and high temperatures. However, the heat transfer was anisotropic for smaller particle sizes.